Banks' regulatory buffers, liquidity networks and monetary policy transmission - Christian Merkl; Stéphanie Stolz (Deutsche Bundesbank, 2006)
Based on a quarterly regulatory dataset for German banks from 1999 to 2004, this paper analyzes the effects of banks' regulatory capital on the transmission of monetary policy in a system of liquidity networks. The dynamic panel regression results provide evidence in favor of the bank capital channel theory. Banks holding less regulatory capital and less interbank liquidity react more restrictively to a monetary tightening than their peers.
Keywords: E52; G21; G28; C23; 330; Bank lending channel; Bank capital channel; Liquidity networks; Monetary policy transmission; Transmissionsmechanismus; Bank; Eigenkapital; Bankenliquidität; Schätzung; Deutschland